Glycation modulates glutamatergic signaling and exacerbates Parkinson’s disease-like phenotypes - Chegão, Ana (2022)
Funding Information: This study was supported by Fundação para a Ciência e Tecnologia (FCT) PTDC/NEU-OSD/5644/2014, by iNOVA4Health UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by FCT/Ministério da Ciência, Tecnologia e Ensino Superior, through national funds; and by Sociedade Portuguesa de Diabetologia. The authors were supported by: A.C. (FCT, PD/BD/136863/2018; ProRegeM – PhD programme, mechanisms of disease and regenerative medicine); B.F.G. (PTDC/NEU-OSD/5644/2014); L.S. (SFRH/BD/143286/2019). T.F.O. is supported by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany’s Excellence Strategy - EXC 2067/1- 390729940, and by SFB1286 (B8). Funding Information: We would like to thank the vivarium and behavioral facilities at Instituto de Medicina Molecular?Jo?o Lobo Antunes for all the support. We also thank Prof. Rosalina Fonseca, Prof. S?lvia V. Conde, Dr Rita Machado de Oliveira, Dr Nat?lia Madeira, Dr Liliana Lopes, Dr Tatiana Burrinha, and Dr Catarina Perdig?o for fruitful discussions. We thank Dr Manuela Correia for all the laboratory support. We are deeply thankful to Prof. Jos? Ramalho for kindly allowing the use of equipment for protein analysis. This study was supported by Funda??o para a Ci?ncia e Tecnologia (FCT) PTDC/NEU-OSD/5644/2014, by iNOVA4Health UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by FCT/Minist?rio da Ci?ncia, Tecnologia e Ensino Superior, through national funds; and by Sociedade Portuguesa de Diabetologia. The authors were supported by: A.C. (FCT, PD/BD/136863/2018; ProRegeM ? PhD programme, mechanisms of disease and regenerative medicine); B.F.G. (PTDC/NEU-OSD/5644/2014); L.S. (SFRH/BD/143286/2019). T.F.O. is supported by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany?s Excellence Strategy - EXC 2067/1- 390729940, and by SFB1286 (B8). Publisher Copyright: © 2022, The Author(s).